Uji Sifat Fisika Tepung Batang Buah Naga Menggunakan Pengering Tipe Rak - Yunia Nisa Fauziah; Budi Hariono (Politeknik Negeri Jember, 2022)
The use of dragon fruit stems as food is still very limited. The development of dragon fruit stems needs to be done by utilizing existing technology, namely by making it into dragon fruit stem flour. This study aims to determine the effect of temperature and drying time on the physical and chemical properties of pitaya stem flour. The experimental design in this study consisted of two factors, namely drying temperature (S Factors) covering S1 (45oC), S2 (55oC), S3 (65oC) and a drying time (L factors) consisting of L1 (18 hours), L2 (21 hours) and L3 (24 hours). The experimental design in the main study used a randomized block design with a 3 x 3 factorial pattern, which was repeated 3 times. The result obtained from this study show that drying temperature and drying time significantly affect the moisture content, ash content, vitamin C, water absorption, fineness modulus, and average diameter of the particles. The interaction of temperature and drying time had a significant effect on moisture content, ash content, vitamin C, color, water absorption, fineness modulus and average diameter but did not affect the yield of pitaya stem flour.